2010
DOI: 10.1111/j.1540-8175.2009.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant Aneurysm of the Right Atrial Appendage

Abstract: A 52-year-old man was referred to our hospital to be evaluated for a heart transplant. He had a history of multiple admissions due to heart failure. His physical examination revealed: jugular distension, hepatomegaly, and peripheral edema. The electrocardiogram showed sinus rhythm with right axis deviation. A chest x-ray revealed cardiomegaly. Transthoracic echocardiography showed an aneurysmal dilatation of the right atrial appendage (RAA) with intracavity thrombus (Fig. 1). The right ventricular ejection fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…12 In patients with difficult TTE images and or unclear diagnosis, TEE with contrast study and has been reported to increase sensitivity for diagnosing RAAA, however, the sensitivity was still low at 33%. 10 Risk factors associated with adverse outcomes including thromboembolic and arrhythmic complications included large RAAA size, large right atrial size, and associated congenital cardiac defects. 13 Both the modalities are useful in confirming the connection of the aneurysm to the RAA and studying its relation to other structures like descending thoracic aorta.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In patients with difficult TTE images and or unclear diagnosis, TEE with contrast study and has been reported to increase sensitivity for diagnosing RAAA, however, the sensitivity was still low at 33%. 10 Risk factors associated with adverse outcomes including thromboembolic and arrhythmic complications included large RAAA size, large right atrial size, and associated congenital cardiac defects. 13 Both the modalities are useful in confirming the connection of the aneurysm to the RAA and studying its relation to other structures like descending thoracic aorta.…”
Section: Resultsmentioning
confidence: 99%
“…CT angiography and MRI are excellent adjuvant imaging tools, in patients in whom the diagnosis is not clear on TEE, with high sensitivity and specificity. 3,6,9,10 Periodic monitoring of RAAA in asymptomatic patients with cardiac MRI or CT for evidence of enlarging RAAA has been shown to be a useful tool in selecting patients for early surgical intervention. 2 A 24-hour Holter recording should be requested in patients complaining of palpitations and/or normal ECG for the evaluation of atrial tachyarrhythmias.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical presentations of RAAA mainly include supraventricular arrhythmia, intracavity thrombosis, and space‐occupying effects such as compression of the tricuspid annulus or compression of the right ventricular outflow tract (RVOT) . Moreover, there have been cases accompanied with right ventricular (RV) dysfunction and pulmonary hypertension (PH), although it remains unclear whether such manifestations were related to the aneurysm. However, clinical characteristics may depend on the location and size of the aneurysm, and some cases are asymptomatic …”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence to suggest that aneurysmectomy and anticoagulation are needed in all situations . However, potential risks of thrombosis and embolism were documented in previous reports . For conservatively treated cases, follow‐up examinations of EKG, Holter and echocardiography are greatly important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation